PENGEMBANGAN SISTEM INFORMASI KEANGGOTAAN HIMPUNAN MAHASISWA TEKNOLOGI INFORMASI INSTITUT TEKNOLOGI DAN BISNIS BANTEN - Adha, Rizki; Nanda Pratama, Febrian; Baejuri, Aang; Daniyah, Dian (Innotech: Jurnal Ilmu Komputer, Sistem Informasi dan Teknologi Informasi, 2024)
The Information Technology Student Association (HMTI) at the Banten Institute of Technology and Business is currently experiencing challenges in the member data collection process which is still done manually. not only is this time consuming, but it also risks losing important data. Therefore, this research aims to update the data collection system with a more efficient approach. Using the Agile Development method, this research will go through several stages, including system analysis, design, development, testing, deployment, revision, and launch. System testing is carried out using the black box method to ensure good functionality. The results of the testing show that the system is in accordance with the desired output and has met the functionality requirements, so that the HMTI membership data processing process can be faster and better organized.